Method for producing composite for secondary battery electrode

The mechanochemical mixing of electrode active material and fibrous carbon dispersion in a non-slurry form addresses the inefficiencies of existing methods, resulting in a highly conductive and uniform composite for secondary battery electrodes, enhancing battery performance and reducing energy consumption.

JP2025007169APending Publication Date: 2025-01-17TOYO INK MFG CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2023108391
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-06-30
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

Existing methods for producing composite particles for secondary battery electrodes require high drying energy to remove solvents, leading to inefficiencies and non-uniform distribution of fibrous carbon, which affects conductivity and uniformity.

Method used

A method involving mechanochemical mixing of electrode active material and fibrous carbon dispersion in a non-slurry form, followed by solvent removal and drying, to achieve uniform adsorption of fibrous carbon on the active material surface, reducing drying energy and enhancing conductivity.

Benefits of technology

This approach results in a highly conductive and uniform composite for secondary battery electrodes, enabling high-output and long-life nonaqueous electrolyte secondary batteries with reduced energy consumption.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025007169000001
    Figure 2025007169000001
  • Figure 2025007169000002
    Figure 2025007169000002
  • Figure 2025007169000003
    Figure 2025007169000003
Patent Text Reader

Abstract

To provide a composite for a secondary battery electrode having excellent electrical conductivity by precisely controlling the dispersion state of fibrous carbon on an active material.SOLUTION: A method for producing a composite for a secondary battery electrode containing an electrode active material and fibrous carbon includes a step of combining an electrode active material and a fibrous carbon dispersion in which the fibrous carbon is dispersed in a solvent in a non-slurry state by using a mechanochemical mixer, and a step of removing the solvent and drying the composite. The fibrous carbon dispersion contains a dispersant composition that satisfies a predetermined condition, fibrous carbon having an average fiber length of 0.3 μm or more, and a medium containing water.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing a composite for a secondary battery electrode. [Background technology]

[0002] With the spread of electric vehicles and the miniaturization, weight reduction, and high performance of portable devices, secondary batteries with high energy density and higher capacity are required. Under such a background, non-aqueous electrolyte secondary batteries using a non-aqueous electrolyte, particularly lithium ion secondary batteries, are being used in many devices because of their characteristics of high energy density and high voltage.

[0003] Furthermore, as the applications of lithium-ion secondary batteries expand, there is a demand not only for improved battery performance, such as higher capacity, faster charging, and longer life, but also for reduced battery costs and a reduced environmental impact in production. In particular, there is a growing need to reduce the environmental impact, which in turn leads to reduced CO2 emissions, and the reduction of energy consumption in the production of lithium-ion secondary batteries, which account for a large portion of the costs and energy consumed in the production of electric vehicles, has become an issue.

[0004] To address the above issues, a method of manufacturing electrodes by powder molding that does not require a composite slurry has been proposed, since a large amount of drying energy is required to remove the solvent in conventional electrode manufacturing methods that use a composite slurry. In electrode manufacturing by powder molding, issues include improving productivity and making the electrode material uniform, so composite particles of active materials are used, which are expected to improve the fluidity of the material and narrow the particle size distribution. For example, Patent Document 1 discloses a method for increasing thickness accuracy at low basis weight during powder molding by controlling the particle size distribution of composite particles produced by spraying and drying a slurry for composite particles containing an electrode active material, a water-soluble polymer, a binder resin, and a dispersion medium. Furthermore, Patent Document 2 discloses an example of producing composite particles with excellent particle strength by spray granulating a slurry containing a positive electrode active material, carbon black, and cellulose nanofibers. In addition, composite particles of active materials are expected to be used not only in powder molding, but also in conventional manufacturing processes using composite slurries. In order to increase the capacity of secondary batteries, it is essential to increase the active material ratio in the electrode, so it is necessary to reduce the amount of auxiliary components. For this reason, the use of fibrous carbon, which has a small outer diameter and long fiber length and can form a conductive network with a small amount of addition, is seen as a promising conductive agent. However, it is difficult to distribute it uniformly in the electrode because it conflicts with the large cohesive force. Therefore, a method has been proposed that uses composite particles with fibrous carbon adsorbed on the surface of the active material in advance. For example, Patent Document 3 discloses an example in which positive electrode active material particles and fibrous carbon are dispersed in a solvent using an ultrasonic disperser, and the resulting slurry is spray-granulated to produce composite particles in which the materials are uniformly mixed, and the composite particles are then made into an electrode after preparing a composite slurry. Furthermore, Patent Document 4 discloses an example in which a positive electrode active material and carbon nanotubes are combined in a nitrogen atmosphere by mechanochemical treatment to produce a positive electrode active material having high electronic conductivity and high mechanical strength. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Patent No. 6954424 [Patent Document 2] Patent No. 6380526 [Patent Document 3] Patent No. 5377946 [Patent Document 4] JP 2016-201228 A Summary of the Invention [Problem to be solved by the invention]

[0006] The methods disclosed in Patent Documents 1 to 3 require a spray granulation process when producing composite particles. A slurry in which the materials are uniformly dispersed is sprayed and instantly dried in a heating tank, making it possible to produce homogeneous composite particles. However, in order to spray the slurry in a spray form, it is necessary to reduce the viscosity of the slurry, and there is a limit to how much solid can be produced. Therefore, a larger amount of solvent is required than that used in conventional composite slurries, and the effect of reducing energy consumption in electrode production is not significant. In the method disclosed in Patent Document 4, composite particles can be produced without using a solvent because the carbon nanotubes are mixed in a powder state. However, it is difficult to disentangle the fibrous and entangled carbon nanotubes during the composite process, and the carbon nanotubes are not uniformly adsorbed onto the active material surface, resulting in non-uniform composite particles, making it difficult to form a uniform conductive network in the electrode.

[0007] The present invention aims to provide a method for producing composite particles that can solve the above-mentioned problems, i.e., reduce the drying energy required to remove the solvent during electrode production, while also achieving a uniform composite of highly cohesive fibrous carbon and active material, and to provide a composite for secondary battery electrodes that can achieve high conductivity even in the electrode. [Means for solving the problem]

[0008] The present invention relates to a method for producing a composite for a secondary battery electrode, comprising an electrode active material and fibrous carbon, the method comprising the steps of: combining an electrode active material and a fibrous carbon dispersion in which the fibrous carbon is dispersed in a solvent in a non-slurry state using a mechanochemical mixer; and removing the liquid medium and drying the composite.

[0009] The present invention also provides a method for producing a composite for a secondary battery electrode, comprising an electrode active material and fibrous carbon, the method comprising the steps of: combining an electrode active material and a fibrous carbon dispersion in which the fibrous carbon is dispersed in a solvent in a non-slurry state using a mechanochemical mixer; and removing the solvent and drying the resulting mixture. The present invention relates to a method for producing a secondary battery electrode composite, characterized in that the fibrous carbon dispersion contains a dispersant composition that satisfies the following (1) and (2), fibrous carbon having an average fiber length of 0.3 μm or more, and a medium containing water, and satisfies the following (3): (1) Nitrile group-containing structural unit, carboxyl group-containing structural unit, hydroxyl group-containing structure units, and heterocyclic ring-containing structural units, The polymer (A) has a weight average molecular weight of 5,000 or more and 360,000 or less. (2) A component (B) other than the polymer, which is derived from the raw material of the polymer (A), is added to the dispersant composition. The content is 1.5 mass% or less based on mass. (3) The particle size D10 at the cumulative 10% of the particle size distribution measured by dynamic light scattering is 50n m or more.

[0010] The present invention also relates to the method for producing a composite for a secondary battery electrode, wherein the fibrous carbon dispersion has a particle size D50 at a cumulative 50% of a particle size distribution measured by a dynamic light scattering method of less than 3000 nm.

[0011] The present invention also relates to the method for producing a composite for a secondary battery electrode, wherein the polymer (A) contains 5 mass % or less of a polymer (E) having a molecular weight of less than 1,000, based on the mass of the polymer (A).

[0012] The present invention also relates to a method for producing the above composite for a secondary battery electrode, wherein the fibrous carbon has an exothermic peak temperature of 520°C or lower as measured by simultaneous thermogravimetry-differential thermal analysis under an oxygen atmosphere.

[0013] The present invention also relates to a method for producing the composite for a secondary battery electrode, wherein the composite for a secondary battery contains a binder resin.

[0014] The present invention also relates to a method for producing an electrode film formed by using the electrode composite for secondary batteries obtained by the method for producing an electrode composite for secondary batteries.

[0015] The present invention also relates to a method for producing a secondary battery including an electrode film obtained by the method for producing an electrode film. Effect of the Invention

[0016] According to an embodiment of the present invention, a composite for a secondary battery electrode having excellent electrical conductivity can be provided by precisely controlling the dispersion state of the fibrous carbon on the active material. According to still another embodiment of the present invention, a high-output, long-life non-aqueous electrolyte secondary battery and an electrode film used therein can be provided. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0017] Hereinafter, a method for producing a composite for a secondary battery electrode according to an embodiment of the present invention will be described in detail. The present invention is not limited to the following embodiment, and the present invention also includes embodiments that are implemented within the scope of the present invention.

[0018] In this specification, carbon nanotubes may be referred to as "CNTs." Hydrogenated nitrile rubber may be referred to as "H-NBR," and N-methyl-2-pyrrolidone may be referred to as "NMP." In this specification, carbon nanotube dispersions may be simply referred to as "CNT dispersions" or "dispersions." Additionally, composites for secondary battery electrodes may be referred to as "composite for electrodes" or "composite."

[0019] <Method of manufacturing a composite for secondary battery electrode> The method for producing an electrode composite for a secondary battery of the present invention is characterized by including a step of combining an electrode active material and a fibrous carbon dispersion in which fibrous carbon is dispersed in a solvent in a non-slurry state using a mechanochemical mixer, and a step of removing the liquid medium and drying the resulting mixture.

[0020] In the process for producing the composite for secondary battery electrode of the present invention, the inclusion of the following (1) to (3) is an important factor for producing a composite having good resistance characteristics. (1) Uses a dispersion of fibrous carbon (2) Controlling the state of the mixture of the electrode active material and the dispersed carbon fiber (3) Compounding in a mechanochemical mixer The reasons for this will be explained below. (1) In order to adsorb fibrous carbon to the surface of an active material in the form of disintegrated primary particles or bundle particles, it is necessary to disintegrate the fibrous carbon, which has strong cohesive power, to the above-mentioned state, and dispersion in a liquid phase state (slurry) is essential for this. However, if it is combined with an active material in a slurry state, it is not possible to reduce the energy required to dry the solvent involved in electrode production. Therefore, it is necessary to use a dispersion of fibrous carbon in which the primary particles or bundle particles of fibrous carbon are uniformly dispersed and stabilized in advance. (2) By forming a composite in a non-slurry state with a high solid content concentration, it is possible to reduce the total amount of drying energy of the solvent in the electrode manufacturing using a conventional composite slurry. In addition, when the mixture is in a non-slurry state, it does not have fluidity as a liquid, so even if the composition has a smaller resin content than a general composite slurry, separation of components during drying and drying aggregation of fibrous carbon can be suppressed. The solid content concentration of the non-slurry mixture is preferably 60 mass% or more, and more preferably 80 mass% or more. The state of the mixture changes depending on the content of the solvent. In the order of the solvent content, it changes to a slurry state (with liquid fluidity), a clay-like state (without liquid fluidity, with viscosity), a crumbly state (without liquid fluidity, without viscosity), and a powder state (absolutely dry). In the present invention, the non-slurry state refers to a clay-like or crumbly state, but in order to suppress drying aggregation, mixing in a crumbly state is more preferable. (3) By mixing in a non-slurry state, it is expected that drying aggregation can be suppressed, but since it cannot flow as a liquid, the dispersion of fibrous carbon is difficult to wet and spread on the active material surface, and it is likely to become uneven. Therefore, by using a mechanochemical mixer capable of applying shear force to press the dispersion of fibrous carbon against the active material surface and promote wetting and spreading, it is expected that the fibrous carbon can be evenly adsorbed onto the active material surface while loosening the fibrous carbon. The above (1) to (3) reduce the amount of drying energy required to prepare an electrode, allow the fibrous carbon to be evenly adsorbed onto the surface of the active material in a loosened state, and prevent separation of the components and aggregation of the fibrous carbon during drying during the process of concentrating and evaporating the solvent, thereby making it possible to obtain a highly conductive composite and electrode.

[0021] <Mechanochemical mixing device> The mechanochemical mixer is not particularly limited as long as it is a device capable of mixing a non-slurry mixture by applying a shear force. Examples of such machines include high-speed mixers such as the Henschel Mixer and Super Mixer, particle compounding devices "Nanocure", "Nobilta", and "Mechanofusion" manufactured by Hosokawa Micron Corporation, powder surface modification device "Miraro" manufactured by Nara Machinery Works, "Hivismix" and "Hivisdepermix" manufactured by Primix, mixers "Planetary Mixer" and "Trimix" manufactured by Inoue Manufacturing Co., Ltd., and mixer / granulator "High Speed ​​Mixer" manufactured by EarthTechnica Corporation. Among the mechanochemical mixers, planetary mixers, trimixes, and mechanofusions are preferred because they are capable of shear compounding and uniform mixing of materials.

[0022] <Electrode active material> The electrode active material is a material that causes a battery reaction required to extract electrical energy, and is not particularly limited. As the positive electrode active material, for example, for secondary battery applications, metal compounds such as metal oxides and metal sulfides that can reversibly dope or intercalate lithium ions can be used. For example, lithium manganese composite oxides (e.g., Li x Mn2O4 or Li x MnO2), lithium nickel composite oxide (e.g. Li x NiO2), lithium cobalt complex oxide (Li x CoO2), lithium nickel cobalt complex oxide (e.g. Li x Ni 1-y Co y O2), lithium manganese cobalt complex oxide (e.g. Li x Mn yCo 1-y (O2), lithium nickel manganese cobalt composite oxide (e.g., Li x Ni y Co z Mn 1-y-z O2), spinel-type lithium manganese nickel composite oxide (e.g., Li x Mn 2-y Ni y O4), etc., composite oxide powders of lithium and transition metals, lithium phosphate powders having an olivine structure (e.g., Li x FePO4, Li x Fe 1-y Mn y PO4, Li x CoPO4, etc.), manganese oxide, iron oxide, copper oxide, nickel oxide, vanadium oxides (e.g., V2O5, V6O 13 ), transition metal oxide powders such as titanium oxide, iron sulfate (Fe2(SO4)3), transition metal sulfide powders such as TiS2, and FeS, etc. However, x, y, z are numbers, 0 < x < 1, 0 < y < 1, 0 < z < 1, 0 < y + z < 1. These positive electrode active materials can also be used alone or in combination of two or more. Among these active materials, in particular, active materials containing Ni and / or Mn (especially when the total amount of Ni and / or Mn in the transition metal is 50 mol% or more) tend to become highly basic due to elution of components derived from raw materials or metal ions, and gelation of the binder resin and deterioration of the dispersion state are likely to occur due to this effect. Therefore, in the case of a battery containing an active material containing Ni and / or Mn, the present embodiment is particularly effective.

[0023] As the negative electrode active material, for example, metal Li capable of reversibly doping or intercalating lithium ions, or its alloy, tin alloy, silicon-based material (such as metallic Si, Si alloy, SiOx), LiXTiO2, LiXFe2O3, LiXFe3O4, LiXWO2, etc. of metal oxide-based, polyacetylene, poly-p-phenylene and other conductive polymers, highly graphitized carbon materials such as artificial graphite, or carbonaceous powders such as natural graphite, resin-fired carbon materials can be used. However, x is a number and 0 < x < 1. These negative electrode active materials can be used alone or in combination of two or more. In particular, when using a silicon-based material, although the theoretical capacity is large, the volume expansion is extremely large, so it is preferably used in combination with artificial graphite such as highly graphitized carbon materials, or carbonaceous powders such as natural graphite, resin-fired carbon materials, etc.

[0024] <Fibrous carbon> Fibrous carbon is a fibrous carbon material, with a high aspect ratio in the c-axis direction, and it is easier to form a conductive network compared to particulate carbon such as carbon black. Examples of fibrous carbon include carbon fiber (CNF) and carbon nanotube (CNT). Fibrous carbon has a shape in which planar graphite is wound into a cylindrical shape, including single-layer fibrous carbon, double-layer fibrous carbon, thin-layer (several layers) fibrous carbon, multi-layer fibrous carbon, and these may be mixed. Single-layer fibrous carbon has a structure in which one layer of graphite is wound. Multi-layer fibrous carbon has a structure in which two or more layers of graphite are wound. Also, the side wall of the fibrous carbon does not have to be a graphite structure. Also, for example, fibrous carbon having a side wall with an amorphous structure is also fibrous carbon in this specification.

[0025] The shape of the fibrous carbon is not limited. Such shapes include various shapes including needle-like, cylindrical tube-like, fishbone-like (fishbone or cup stacking type), platelet-like (platelet), and coil-like. Among them, the shape of the fibrous carbon is preferably needle-like or cylindrical tube-like. The fibrous carbon may be of a single shape or a combination of two or more shapes.

[0026] Examples of the form of fibrous carbon include graphite whiskers, filamentous carbon, graphite fibers, ultrafine carbon tubes, carbon tubes, carbon fibrils, carbon microtubes, and carbon nanofibers. The carbon nanotubes may have a form consisting of a single one of these or a combination of two or more of these.

[0027] The average outer diameter of the fibrous carbon is preferably 100 nm or less, more preferably 50 nm or less. If the average outer diameter is too large, it may be difficult to uniformly combine with the composite. Also, it is preferably 30 nm or less, more preferably 20 nm or less, and even more preferably 13 nm or less. Also, it is preferably 1 nm or more, and more preferably 3 nm or more. The average outer diameter of the fibrous carbon can be calculated by observing and photographing the fibrous carbon with a transmission electron microscope, randomly selecting 300 pieces of fibrous carbon from the observation photograph, and measuring the outer diameter of each piece.

[0028] <Polymer (A)> The polymer (A) of the present invention contains at least one of a nitrile group-containing structural unit, a carboxyl group-containing structural unit, a hydroxyl group-containing structural unit, and a heterocyclic ring-containing structural unit. The weight average molecular weight of the polymer (A) is 5,000 or more and 360,000 or less. The polymer (A) preferably contains an alkylene structure in the main chain, and by having any one of a nitrile group, a carboxyl group, a hydroxyl group, and a heterocyclic ring structure having strong polarization, the adsorption to the fibrous carbon and the affinity to the medium can be increased, and the fibrous carbon can be stably present in the medium. In addition, when the polymer (A) contains two or more selected from the group consisting of a nitrile group-containing structural unit, a carboxyl group-containing structural unit, a hydroxyl group-containing structural unit, and a heterocyclic ring-containing structural unit, the adsorption to the fibrous carbon and the affinity to the medium can be further increased, which is more preferable.

[0029] The weight average molecular weight of the polymer (A), in terms of polystyrene, is preferably 5,000 or more, more preferably 6,000 or more, and even more preferably 8,000 or more. Also, it is preferably 360,000 or less, more preferably 260,000 or less, and even more preferably 100,000 or less. If the polymer has an appropriate weight average molecular weight, the adsorption to the dispersed material is improved, and the stability of the dispersion is further improved.

[0030] The nitrile group-containing structural unit is a structural unit containing a nitrile group, and preferably contains a structural unit containing an alkylene structure substituted with a substituent containing a nitrile group. The alkylene structure is preferably a linear or branched alkylene structure. The number of nitrile groups contained in the nitrile group-containing structural unit is preferably one or two, more preferably one. The method of introducing the nitrile group-containing structural unit into the polymer (A) is not particularly limited, but for example, a method of preparing a polymer by polymerization reaction of a monomer containing a nitrile group can be preferably used.

[0031] Examples of monomers containing a nitrile group include acrylonitrile, methacrylonitrile, and fumaronitrile, and one type can be used alone or two or more types can be used in combination. When the monomer containing a nitrile group is acrylonitrile, the copolymer is less bent, and adjacent cyano groups are oriented to form a partial structure with strong polarization, so that the intermolecular forces between polymers and between a polymer and fibrous carbon are high. From the viewpoint of increasing the intermolecular forces, and from the viewpoint of availability and reactivity of raw materials, it is preferable that the monomer containing a nitrile group is acrylonitrile. From the viewpoint of increasing the intermolecular forces, the content of the nitrile group-containing structural unit is preferably 30% by mass or more, more preferably 45% by mass or more, and even more preferably 60% by mass or more, and also preferably 100% by mass or less, more preferably 93% by mass or less, and even more preferably 87% by mass or less, when the mass of the polymer (excluding the initiator and the chain transfer agent) is 100% by mass. By setting the content of the nitrile group-containing structural unit within the above range, the fibrous carbon can be stably present in the medium. Furthermore, when the dispersant is used in a secondary battery, it is possible to prevent problems such as an increase in the resistance of the electrolyte caused by the dissolution of the dispersant in the electrolyte in the battery.

[0032] The carboxyl group-containing structural unit is a structural unit containing a carboxyl group, and preferably contains a structural unit containing an alkylene structure substituted with a substituent containing a carboxyl group. The alkylene structure is preferably a linear or branched alkylene structure. The number of carboxyl groups contained in the carboxyl group-containing structural unit is preferably one or two, more preferably one. The method of introducing the carboxyl group-containing structural unit into the polymer (A) is not particularly limited, but examples thereof include a method of preparing a polymer by polymerization reaction of a monomer containing a carboxyl group, or a method of preparing a polymer by polymerization reaction of a monomer containing a functional group other than a carboxyl group, and modifying the polymer to a carboxyl group. In particular, the method of preparing a polymer by polymerization reaction of a monomer containing a carboxyl group can be preferably used.

[0033] Examples of monomers containing a carboxyl group include unsaturated fatty acids such as (meth)acrylic acid, crotonic acid, itaconic acid, maleic acid, fumaric acid, and citraconic acid, 2-(meth)acryloyloxyethyl phthalate, 2-(meth)acryloyloxypropyl phthalate, 2-(meth)acryloyloxyethyl hexahydrophthalate, 2-(meth)acryloyloxypropyl hexahydrophthalate, ethylene oxide-modified succinic acid (meth)acrylate, and β-carboxyethyl (meth)acrylate. In addition, examples of monomers containing a carboxyl group include acid anhydride-containing monomers such as maleic anhydride, itaconic anhydride, and citraconic anhydride, which are polymers of the above-mentioned carboxyl group-containing monomers, and monofunctional alcohol adducts thereof. A group having a structure in which two carboxyl groups are dehydrated and condensed, "-C(=O)-OC(=O)-" (herein referred to as an "acid anhydride group"), also forms a carboxyl group upon hydrolysis, and is therefore included in the carboxyl group herein. A carboxyl group-containing monomer may also be obtained by hydrolyzing the carbamoyl group of a polymer obtained by polymerization of a monomer containing a carbamoyl group, such as (meth)acrylamide. The carboxyl group-containing monomer is preferably an unsaturated fatty acid, more preferably (meth)acrylic acid, and even more preferably acrylic acid.

[0034] From the viewpoint of having a suitable affinity with the medium (D), the content of the carboxyl group-containing structural unit is preferably 40% by mass or more, more preferably 60% by mass or more, even more preferably 80% by mass or more, and preferably 98% by mass or less, and may be 100% by mass, when the mass of the polymer (excluding the initiator and the chain transfer agent) is 100% by mass. In addition, if one or more selected from the group of a nitrile group-containing structural unit, a hydroxyl group-containing structural unit, and a heterocyclic ring-containing structural unit are further contained, the affinity between the fibrous carbon and the medium is increased, which is more preferable. When one or more selected from the group of a nitrile group-containing structural unit, a hydroxyl group-containing structural unit, and a heterocyclic ring-containing structural unit are further contained, the content of the carboxyl group-containing structural unit is preferably 3% by mass or more, more preferably 9% by mass or more, and even more preferably 14% by mass or more, when the mass of the polymer (excluding the initiator and the chain transfer agent) is 100% by mass. Furthermore, from the viewpoint of electrolyte resistance and prevention of moisture absorption during storage, the content is preferably 47% by mass or less, more preferably 37% by mass or less, and even more preferably 27% by mass or less, based on the mass of the polymer (i.e., when the mass of the polymer is 100% by mass).

[0035] The hydroxyl group-containing structural unit is a structural unit containing a hydroxyl group, and preferably contains a structural unit containing an alkylene structure substituted with a substituent containing a hydroxyl group. The alkylene structure is preferably a linear or branched alkylene structure. The number of hydroxyl groups contained in the hydroxyl group-containing structural unit is preferably one or two, more preferably one. The method of introducing the hydroxyl group-containing structural unit into the polymer (A) is not particularly limited, but examples thereof include a method of preparing a polymer by polymerization reaction of a monomer containing a hydroxyl group, or a method of preparing a polymer by polymerization reaction of a monomer containing a functional group other than a hydroxyl group, and modifying the polymer into a hydroxyl group. A reasonable method can be selected from the viewpoint of reactivity and raw material cost.

[0036] Examples of monomers containing a hydroxyl group include 2-hydroxyethyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, glycerol mono(meth)acrylate, 4-hydroxyvinylbenzene, 2-hydroxy-3-phenoxypropyl acrylate, and caprolactone adducts of these monomers (the number of moles added is 1 to 5), etc. The monomer containing a hydroxyl group is preferably a hydroxyalkyl (meth)acrylate, more preferably 2-hydroxyethyl (meth)acrylate, and even more preferably 2-hydroxyethyl acrylate.

[0037] As a method for preparing a polymer by polymerization reaction of a monomer containing a functional group other than a hydroxyl group and modifying it to a hydroxyl group, for example, there is a method in which the acetyl group of polyvinyl acetate obtained by polymerization of vinyl acetate is saponified with an alkali such as sodium hydroxide to convert it to a hydroxyl group (saponification reaction). The saponification reaction rate (saponification degree) can be controlled as desired by changing the concentration of sodium hydroxide and the treatment time.

[0038] In addition, for the purpose of increasing the affinity between the fibrous carbon and the medium, at least a part of the hydroxyl groups in the polymer may be reacted with an aldehyde compound to be modified into an acetal group (acetalization). The aldehyde compound used in the acetalization reaction may be, for example, a linear, branched, cyclic saturated, unsaturated, or aromatic aldehyde compound having 1 to 15 carbon atoms, but is not limited thereto. Specific examples include formaldehyde, acetaldehyde, propionyl aldehyde, n-butyl aldehyde, isobutyl aldehyde, tert-butyl aldehyde, benzaldehyde, and cyclohexyl aldehyde. These aldehyde compounds may be used alone or in combination of two or more kinds. In addition, these aldehyde compounds may be those in which one or more hydrogen atoms are substituted with halogen or the like, except for formaldehyde. From the viewpoint of versatility, linear, branched, cyclic saturated, unsaturated, or aromatic aldehyde compounds having 1 to 10 carbon atoms are preferred, and linear aldehyde compounds having 1 to 4 carbon atoms are more preferred. By changing the aldehyde compound and the treatment time, the reaction rate of acetalization (degree of acetalization) can be arbitrarily controlled.

[0039] The content of the hydroxyl group-containing structural unit is preferably 80% by mass or more, more preferably 85% by mass or more, and more preferably 99.8% by mass or less, when the mass of the polymer (excluding the initiator and the chain transfer agent) is taken as 100% by mass. However, when one or more selected from the group of nitrile group-containing structural units, hydroxyl group-containing structural units, and heterocyclic ring-containing structural units are further contained, the content is preferably 5% by mass or more, preferably 95% by mass or less, and more preferably 85% by mass or less. By setting it to the above range, the polarization can be strengthened and the affinity to the fibrous carbon and the medium can be increased. It is also preferable from the viewpoint of electrolyte resistance. It is particularly preferable to further contain one or more selected from the group of nitrile group-containing structural units, hydroxyl group-containing structural units, and heterocyclic ring-containing structural units, because the polarization becomes stronger. The content of the acetal group is preferably within the preferred range of the content of the hydroxyl group-containing structural units for the same reason as the content of the hydroxyl group-containing structural units.

[0040] The heterocyclic ring-containing structural unit is a structural unit containing a heterocyclic ring, and more preferably a structural unit containing an alkylene structure substituted with a heterocyclic ring-containing substituent. The alkylene structure is preferably a linear or branched alkylene structure. The heterocyclic ring contained in the heterocyclic ring-containing structural unit may be a monocyclic structure or a condensed ring structure, but is preferably a monocyclic structure. The number of heterocyclic rings contained in the heterocyclic ring-containing structural unit is preferably one or two, more preferably one. The heterocyclic ring contains an atom other than carbon in the ring-constituting atoms, for example, one or more nitrogen, oxygen, sulfur atoms, etc. As the atom other than carbon constituting the ring, nitrogen or oxygen is preferable, and nitrogen is more preferable. When the ring-constituting atoms contain an atom other than carbon, polarization occurs in the heterocyclic ring, and it becomes possible to strongly act on the fibrous carbon. The method of introducing the heterocyclic ring into the polymer (A) is not particularly limited, but for example, a method of preparing a polymer by polymerization reaction of a monomer containing a heterocyclic ring can be used.

[0041] As the monomer containing a heterocycle, an N-vinyl cyclic amide structural unit is preferred, and examples thereof include N-vinyl-2-pyrrolidone, N-vinyl-ε-caprolactam, N-vinyl-2-piperidone, N-vinyl-3-morpholinone, N-vinyl-1,3-oxazin-2-one, and N-vinyl-3,5-morpholinedione. In particular, N-vinyl-2-pyrrolidone is preferred from the viewpoint of improving battery characteristics. These may be used alone or in combination of two or more kinds.

[0042] The content of the heterocyclic ring-containing structural unit is preferably 70% by mass or more, more preferably 80% by mass or more, even more preferably 90% by mass or more, particularly preferably 95% by mass or more, and may be 100% by mass, in order to strengthen the polarization and enhance the action on the fibrous carbon, when the mass of the polymer (excluding the initiator and the chain transfer agent) is taken as 100% by mass. However, when one or more selected from the group of nitrile group-containing structural units, carboxyl group-containing structural units, and hydroxyl group-containing structural units are further contained, the content of the heterocyclic ring-containing structural unit is preferably 5% by mass or more, more preferably 10% by mass or more, preferably 95% by mass or less, and more preferably 85% by mass or less, based on the mass of the polymer (i.e., when the mass of the polymer is taken as 100% by mass). When one or more selected from the group of nitrile group-containing structural units, carboxyl group-containing structural units, and hydroxyl group-containing structural units are further contained, the polarity is increased and the electrolyte resistance can be improved, which is more preferable.

[0043] The polymer (A) may further contain, as other structural units, one or more structural units selected from the group consisting of active hydrogen group-containing structural units (excluding carboxyl groups and hydroxyl groups), basic group-containing structural units, and ester group-containing structural units. The above structural units are selected and contained according to the properties such as hydrophilicity, hydrophobicity, acidity, and basicity of the substrate to which the fibrous carbon dispersion of the present invention is applied or the material to be mixed, so that the dispersion can be applied to various uses.

[0044] The content of the other structural units is preferably 20% by mass or less, more preferably 10% by mass or less, and even more preferably 5% by mass or less, from the viewpoint of not impairing the polarization of the polymer (A), when the mass of the polymer (excluding the initiator and the chain transfer agent) is taken as 100% by mass.

[0045] The active hydrogen group-containing structural unit is a structural unit having, for example, a primary amino group, a secondary amino group, a mercapto group, etc. as an active hydrogen group. Here, "primary amino group" means -NH2 (amino group), and "secondary amino group" means a group in which one hydrogen atom on a primary amino group is replaced with an organic residue such as an alkyl group. However, the primary amino group and the secondary amino group in acid amide are not included in the active hydrogen group in this specification.

[0046] Basic group-containing structural unit is a structural unit having basic group.Basic group can be exemplified by tertiary amino group, amide group, etc.In addition, the structural unit having primary amino group and the structural unit having secondary amino group can be included in basic group-containing structural unit, but in the present invention, they are treated as the active hydrogen group-containing structural unit and are not included in basic group-containing structural unit.

[0047] The ester group-containing structural unit is a structural unit having a structure represented by (R1)2C=C-CO-O-R2 (wherein R1 is a hydrogen atom or a methyl group, at least one of which is a hydrogen atom, and R2 is an alkyl group which may have a substituent). Note that those containing the active hydrogen group or the basic group as the alkyl group substituent are treated as the active hydrogen group-containing structural unit or the basic group-containing structural unit, and are not included in the ester group-containing structural unit.

[0048] The method for producing the polymer (A) is not particularly limited, and examples thereof include solution polymerization, suspension polymerization, bulk polymerization, emulsion polymerization, and precipitation polymerization, with solution polymerization or precipitation polymerization being preferred. Examples of the polymerization reaction system include addition polymerization such as ionic polymerization, free radical polymerization, and living radical polymerization, with free radical polymerization or living radical polymerization being preferred. Examples of the radical polymerization initiator include peroxides and azo initiators.

[0049] In the case of radical polymerization, the polymerization initiator is not limited to the following, but examples thereof include di-t-butyl peroxide, lauroyl peroxide, stearyl peroxide, benzoyl peroxide, t-butyl peroxy neodecane, t-butyl peroxy pivalate, dilauroyl peroxide, dicumyl peroxide, t-butylperoxy-2-ethylhexanoate, and 1,1-bis(t-butylperoxy)-3,3,5-trimethyl Examples of the initiator include organic peroxides such as cyclohexane and 1,1-bis(t-butylperoxy)cyclohexane, and general azo-based radical polymerization initiators such as azobisisobutyronitrile, azobisisovaleronitrile, 1,1-azobis(1-cyclohexanecarbonitrile), 2,2'-azobis-4-methoxy-2,4-azobisisobutyronitrile, 2,2'-azobis-2,4-dimethylvaleronitrile, and 2,2'-azobis-2-methylbutyronitrile. These initiators may be used alone or in combination of two or more. These radical polymerization initiators may be used in combination with a suitable reducing agent as a redox initiator. These polymerization initiators are generally used at 1% by mass or less based on the total mass of all monomers used (i.e., when the total mass of all monomers is 100% by mass), and can be appropriately selected in consideration of the temperature at which the polymerization is performed and the half-life of the initiator.

[0050] In the process for producing the polymer (A), the molecular weight of the produced polymer can be controlled using a chain transfer agent or the like within a range that does not impair the object of the present invention. Examples of the chain transfer agent include alkyl mercaptans such as octyl mercaptan, nonyl mercaptan, decyl mercaptan, dodecyl mercaptan, and 3-mercapto-1,2-propanediol, thioglycolic acid esters such as octyl thioglycolate, nonyl thioglycolate, and 2-ethylhexyl thioglycolate, 2,4-diphenyl-4-methyl-1-pentene, 1-methyl-4-isopropylidene-1-cyclohexene, -pinene, and β-pinene. From the standpoint of ease of handling and stability, 3-mercapto-1,2-propanediol, thioglycolic acid esters, 2,4-diphenyl-4-methyl-1-pentene, 1-methyl-4-isopropylidene-1-cyclohexene, α-pinene, β-pinene, and the like are particularly preferred. These can be added appropriately depending on the required molecular weight, but it is generally preferable to use them in the range of 0.001% by mass to 4% by mass based on the total mass of all monomers used (i.e., when the total mass of all monomers is 100% by mass).

[0051] Other molecular weight control methods include a method of changing the polymerization method, a method of adjusting the amount of a polymerization initiator, a method of changing the polymerization temperature, etc. These molecular weight control methods may be used alone or in combination of two or more methods.

[0052] As the chain transfer agent, for example, octyl mercaptan, nonyl mercaptan, and deci polymers are preferable in that they have low odor.

[0053] The amount of the chain transfer agent used is preferably 0.01 to 4 mass% and more preferably 0.1 to 2 mass% based on the mass of the polymer (A) (i.e., when the mass of the polymer (A) is taken as 100 mass%). By setting the amount of the chain transfer agent within the above range, the molecular weight of the polymer (A) of the present invention can be adjusted to a suitable molecular weight range.

[0054] The content of polymer (A) in the fibrous carbon dispersion is preferably determined according to the specific surface area and wettability of the fibrous carbon, and is preferably 2 mass% or more, more preferably 20 mass% or more, and even more preferably 30 mass% or more, based on the mass of the fibrous carbon (i.e., when the mass of the fibrous carbon is taken as 100 mass%), and is preferably 250 mass% or less, more preferably 150 mass% or less, and even more preferably 100 mass% or less.

[0055] <Polymer (E)> The polymer (E) of the present invention is a polymer component contained in the polymer (A) and having a molecular weight of less than 1,000. From the viewpoint of suppressing foaming and facilitating foam breaking and defoaming, the content of the polymer (E) is preferably 5% by mass or less, more preferably 4% by mass or less, and even more preferably 3% by mass or less, based on the mass of the polymer (A) (i.e., when the mass of the polymer (A) is taken as 100% by mass). If the content exceeds the above range, the polymer (E) may dissolve in the electrolyte, increasing the viscosity of the electrolyte and decreasing the dielectric constant of the electrolyte solvent.

[0056] The content of polymer (E) can be measured by general gel permeation chromatography (GPC), for example, by the method described in the Examples. Methods for making polymer (E) 5% by mass or less relative to polymer (A) include optimizing the conditions during production and purifying the polymer. For example, (1) a method for optimizing the polymerization temperature and polymerization time to improve the polymerization reaction rate of the monomer, (2) a method for optimizing the amount of initiator and chain transfer agent to reduce the amount of by-products of low molecular weight components, (3) a reprecipitation method in which a solution containing polymer (A) and polymer (E) is dropped into a poor solvent to precipitate and remove the low molecular weight component polymer (E), and (4) a precipitation polymerization method in which production and purification can be performed simultaneously. Although it depends on the polymer composition, the reprecipitation method and precipitation polymerization method are preferred from the viewpoint of ease of controlling the amount of polymer (E), and the precipitation polymerization method is most preferred from the viewpoint of simplicity.

[0057] The component (B) and polymer (E) of the present invention are generated in the synthesis process of the polymer (A), and may remain without being completely separated from the polymer (A). In the present invention, a composition containing the polymer (A) and the component (B) can be used as a dispersant. The polymer (A) may contain the polymer (E). In addition, it is preferable that the dispersant composition does not contain an emulsifier and / or a surfactant. The emulsifier and the surfactant are likely to dissolve in the electrolyte, and there is a concern that they may deteriorate the electrolyte resistance.

[0058] <Ingredient (B)> The component (B) of the present invention is a component other than the polymer derived from the raw material of the polymer (A), and includes at least one selected from the group consisting of unreacted raw materials and by-products generated in the polymerization reaction or the modification reaction. Examples of the unreacted raw materials include the monomers containing a nitrile group, monomers containing a carboxyl group, monomers capable of generating a carboxyl group by modification (e.g., acrylamide, etc.), monomers containing a hydroxyl group, monomers capable of generating a hydroxyl group by modification (e.g., vinyl acetate, etc.), aldehydes, monomers containing a heterocycle, polymerization initiators, chain transfer agents, etc., which are exemplified in the polymer (A). Examples of by-products generated in the polymerization reaction or the modification reaction include metal salts such as sodium salts, potassium salts, and lithium salts of the unreacted raw materials, organic salts such as ammonium salts and amine salts, acetic acid, sodium acetate, compounds generated when a polymerization initiator is deactivated without polymerization, and compounds generated when a chain transfer agent is deactivated without polymerization.

[0059] Since component (B) has a highly polar structure with strong ions or polarization, it may cause foaming in a medium containing water. In addition, if it remains in the electrode film, it may dissolve into the electrolyte and reduce the conductivity of the electrolyte. From the viewpoint of suppressing foaming and adverse effects on the electrolyte, the content of component (B) is preferably 2% by mass or less, more preferably 1.5% by mass or less, even more preferably 1% by mass or less, and particularly preferably 0.5% by mass or less, based on the mass of the dispersant composition (i.e., when the mass of the dispersant composition is 100% by mass). In addition, it is preferably 0.001% by mass or more, and more preferably 0.005% by mass or more. Among these, for the same reason, the content of the polymerization initiator and the compound generated by the polymerization initiator not polymerizing and deactivating is preferably 1% by mass or less, more preferably 0.5% by mass or less, based on the mass of the dispersant composition (i.e., when the mass of the dispersant composition is 100% by mass). For the same reason, the content of the chain transfer agent and the compound generated when the chain transfer agent is deactivated without being polymerized is preferably 1 mass % or less, and more preferably 0.5 mass % or less, based on the mass of the dispersant composition (i.e., when the mass of the dispersant composition is 100 mass %).

[0060] The content of component (B) can be determined from the sum of the amount of volatile components in the dispersant composition and the amount of salt components determined by ion chromatography. More specifically, the structure and content can be determined by gas chromatography analysis of the dispersant composition.

[0061] The structure and content of component (B) by gas chromatography are calculated, for example, under the following measurement conditions, but can be appropriately adjusted depending on the types of compounds expected from the raw materials and structure of the polymer. Analytical equipment: Gas chromatography (GC-2025, Shimadzu Corporation) Solvent: DMF Capillary column: GL Science DB-5MS Column temperature conditions: 60°C hold for 5 minutes, then heat to 100°C (5°C / min, H 0 min), then heat to 280°C (20°C / min, hold for 5 min) Carrier gas: Helium (35kPa) Inlet temperature: 110℃

[0062] Methods for reducing the content of component (B) include optimizing the production conditions and purifying the polymer. Methods for optimizing the production conditions include, for example, when producing polymer (A) by radical polymerization in a solution, optimizing the polymerization temperature and polymerization time to improve the polymerization reaction rate of the monomer, and optimizing the selected initiator to suppress the generation of low molecular weight components (B) such as initiator residues. Methods for purifying the polymer include a method for removing the low molecular weight component (B) during the production stage and a method for removing the low molecular weight component (B) after production. Examples of methods for removing the low molecular weight component (B) during the production stage include a precipitation polymerization method in which the target polymer (A) is obtained by filtration and the low molecular weight component (B) is removed by filtration and washing, and a method in which a large amount of water or a solvent is added to the polymer (A) liquid produced by emulsion polymerization or solution polymerization, and the concentration is adjusted while removing the low molecular weight component (B) by distillation. Examples of methods for removing the low molecular weight component (B) after production include a reprecipitation method in which the polymer (A) solution produced in a solution is dropped into a poor solvent to cause precipitation, and the low molecular weight component (B) is removed by filtration and washing, and a method in which the component (B) that could not be removed by the reprecipitation method is removed by drying under reduced pressure. Although it depends on the polymer composition, from the viewpoint of ease of control of the amount of component (B), the reprecipitation method and the precipitation polymerization method are preferred, and from the viewpoint of simplicity, the precipitation polymerization method is most preferred.

[0063] <Solvent (dispersion medium)> The dispersion medium contains water and may contain, optionally, a water-soluble solvent, such as alcohols such as ethanol, propanol, butanol, methyl cellosolve, butyl cellosolve, and propylene glycol monomethyl ether, and N-methyl-2-pyrrolidone (NMP).

[0064] <Carbon fiber dispersion> The fibrous carbon dispersion contains fibrous carbon and a dispersion medium, and optionally contains a dispersant. The fibrous carbon dispersion may contain optional components such as other additives such as wetting agents, surfactants, pH adjusters, wetting penetrants, and leveling agents, other fibrous carbon, and other polymer components, as necessary, within a range that does not impair the object of the present invention. The optional components can be added at any timing, such as before preparing the dispersion, during dispersion, after dispersion, or a combination thereof.

[0065] The pH of the fibrous carbon dispersion is preferably 7.0 to 10.5, more preferably 9.0 to 10.5. If the pH is below the above range, the fibrous carbon dispersion is likely to gel. If the pH is above the above range, problems such as corrosion of various raw materials and exterior materials in the battery, or gelation of the binder are likely to occur. The pH can be measured by a general pH meter.

[0066] The dispersibility of fibrous carbon in the fibrous carbon dispersion can be evaluated by the complex modulus and phase angle measured by dynamic viscoelasticity measurement. The complex modulus indicates the hardness of the fibrous carbon dispersion, and the better the dispersibility of the fibrous carbon is and the lower the viscosity of the fibrous carbon dispersion, the smaller the complex modulus. However, when the fiber length of the fibrous carbon is large, even if the fibrous carbon is uniformly and stably dissolved in the medium, the complex modulus may be a high value because of the structural viscosity of the fibrous carbon itself. In addition, the phase angle means the phase shift of the stress wave when the strain applied to the fibrous carbon dispersion is a sine wave, that is, it indicates the ease of flow of the dispersion. If it is a pure elastic body, it will be a sine wave in phase with the applied strain, and the phase angle will be 0°. On the other hand, if it is a pure viscous body, it will be a stress wave that has advanced by 90°. In a typical viscoelasticity measurement sample, the phase angle is a sine wave greater than 0° and less than 90°, and if the dispersibility of the fibrous carbon in the fibrous carbon dispersion is good, the phase angle approaches 90°, which is the value of a pure viscous body. However, as with the complex modulus, if the fibrous carbon itself has structural viscosity, the phase angle may be a low value even if the fibrous carbon is uniformly and stably dissolved in the medium.

[0067] The complex modulus of the fibrous carbon dispersion is preferably 50 Pa or less, more preferably less than 20 Pa, more preferably 10 Pa or less, and even more preferably 5 Pa or less. The complex modulus of the fibrous carbon dispersion is preferably 0.01 Pa or more, more preferably 0.05 Pa or more, and even more preferably 0.1 Pa or more. The phase angle of the fibrous carbon dispersion is preferably 5° or more, more preferably 19° or more, even more preferably 30° or more, and particularly preferably 45° or more. The phase angle of the fibrous carbon dispersion is preferably 90° or less, more preferably 85° or less, and even more preferably 80° or less. The complex modulus and phase angle can be measured by the method described in the examples.

[0068] The complex modulus and phase angle of the fibrous carbon dispersion are determined by the dispersibility of the fibrous carbon in the fibrous carbon dispersion, the entanglement of the fibrous carbon, CMC, and other resin components, or the influence of their intermolecular forces, etc., so when the complex modulus X (Pa) and the phase angle Y (°) are in the above-mentioned preferred range, and the product (X×Y) of these is 100 to 1,500, a fibrous carbon dispersion with excellent dispersion stability can be obtained, and further, an electrode film with very good conductivity can be obtained by forming an excellent conductive network. In addition, CMC with a weight average molecular weight of 10,000 to 100,000 and an etherification degree of 0.5 to 0.9 has a small viscoelasticity by itself, but when the product (X×Y) of the complex modulus X (Pa) and the phase angle Y (°) when made into a fibrous carbon dispersion is 100 to 1,500, it can play the role of a thickener or binder used as an electrode composition for a secondary battery, improving the electrode strength and improving the battery performance. It is more preferable that the complex modulus is 50 Pa or less and the phase angle is 15° or more. It is not enough that the viscosity of the fibrous carbon dispersion is low and the (apparent) dispersibility is good, but it is particularly effective to judge the dispersion state by combining the complex modulus and the phase angle with conventional indicators such as viscosity.

[0069] The dispersibility of the fibrous carbon in the fibrous carbon dispersion liquid can also be evaluated by the median diameter (μm) determined by a dynamic light scattering type or laser diffraction / scattering type particle size distribution meter. With the median diameter (μm) determined by each type of particle size distribution meter, the particle size of the fibrous carbon aggregated particles can be estimated by the scattered light intensity distribution by the particles. The median diameter (μm) is preferably 0.5 to 5.0, more preferably 0.5 to 2.0. By setting it within the above range, a fibrous carbon dispersion liquid in an appropriate dispersion state can be obtained. If it is below the above range, fibrous carbon in an aggregated state will exist, and if it exceeds the above range, a large number of finely cut fibrous carbons will be generated, which may make it difficult to form an efficient conductive network. The median diameter can be measured by the method described in the examples.

[0070] The dispersibility of fibrous carbon in the fibrous carbon dispersion can also be evaluated by measuring the gloss (i.e., the intensity of reflected light at an incident angle of 60°) of a coating film obtained by coating on a smooth glass substrate, baking and drying. For example, 1 mL of the fibrous carbon dispersion is dropped onto a smooth glass substrate, coated with a No. 7 bar coater at 2 cm / sec, baked in a hot air oven at 140°C for 10 minutes, and allowed to cool to obtain a coating film. Using a gloss meter (BYKGardner gloss meter microgross60°), three locations on the coating film surface, excluding the ends, are randomly selected, and the average value measured once each can be used as the gloss at 60°. The better the dispersibility of the light incident on the coating film, the smoother the coating film surface becomes, and the higher the gloss. Conversely, the worse the dispersibility, the lower the gloss becomes, as light scattering occurs due to the unevenness of the coating film surface. The gloss at 60° can be measured by the method described in the examples. The gloss is preferably 5 or more, more preferably 50 or more, even more preferably 60 or more, and particularly preferably 70 or more. Also, it is preferably 120 or less, and even more preferably 110 or less. By setting it within the above range, a fibrous carbon dispersion liquid in an appropriate dispersion state can be obtained. If it is below the above range, fibrous carbon in an aggregated state is present, and if it is above the above range, a large amount of finely cut fibrous carbon is generated, making it difficult to form an efficient conductive network.

[0071] The TI value of the fibrous carbon dispersion can be calculated by dividing the viscosity (mPa·s) at 60 rpm measured with a Brookfield viscometer by the viscosity (mPa·s) at 6 rpm. The TI value is preferably 2.0 or more and 5.0 or less. The higher the TI value, the greater the structural viscosity caused by the entanglement of the fibrous carbon, CMC, and other resin components, or their intermolecular forces, and the lower the TI value, the smaller the structural viscosity. By setting the TI value within the above range, it is possible to suppress the entanglement of the fibrous carbon, CMC, and other resin components while allowing these intermolecular forces to act appropriately.

[0072] The fiber length of the fibrous carbon in the fibrous carbon dispersion of the present invention is preferably 0.3 to 5 μm, and more preferably 0.5 to 3.5 μm.

[0073] The cumulative particle size D10 of the fibrous carbon dispersion of this embodiment measured by the dynamic light scattering method is 50 nm or more. Among them, it is preferably 100 nm or more, more preferably 200 nm or more, particularly preferably 300 nm or more, and preferably less than 500 nm, more preferably less than 400 nm. The cumulative particle size D50 of the fibrous carbon dispersion measured by the dynamic light scattering method is preferably 200 nm or more, and preferably less than 3000 nm, more preferably less than 2000 nm, and even more preferably less than 1500 nm. The particle size measured by the dynamic light scattering method is correlated with the length of the fibrous carbon in the dispersion, and the fibrous carbon dispersion in which the cumulative particle size D10 and D50 are in the above range has a good dispersion state of the fibrous carbon in the dispersion. In addition, when the cumulative particle size D10 exceeds the above range, the fibrous carbon in an aggregated state exists, and when the cumulative particle size D10 exceeds the above range, a large number of finely cut fibrous carbons are generated, so that it is difficult to form an efficient conductive network. In particular, when the cumulative particle size D10 is below the above range, the fibrous carbon is broken and contains a large amount of fibrous carbon in an excessively dispersed state, making it difficult to form a developed conductive network. The cumulative particle size D10 and the cumulative particle size D50 can be measured using a general dynamic light scattering measuring device, but more specifically, they can be measured by the method described in the Examples. In this specification, the cumulative particle size D10 and the cumulative particle size D50 may be simply referred to as "D10" and "D50", respectively.

[0074] <Distribution method> The fibrous carbon dispersion of the present invention is preferably produced, for example, by finely dispersing a composition containing a dispersant, fibrous carbon, and a medium through a dispersion treatment using a dispersion device. The dispersion treatment may be carried out in two or more stages by arbitrarily adjusting the timing of addition of the materials to be used.

[0075] Examples of the dispersion device include a kneader, a two-roll mill, a three-roll mill, a planetary mixer, a ball mill, a horizontal sand mill, a vertical sand mill, an annular bead mill, an attritor, a high shear mixer, a high pressure homogenizer, and an ultrasonic homogenizer. In particular, from the viewpoint of promoting the wetting of the fibrous carbon and dissolving coarse particles, it is most preferable to use a high shear mixer in the initial dispersion step, and then to disperse the fibrous carbon while maintaining its fiber length. In addition, by dispersing the fibrous carbon with a high pressure homogenizer and then dispersing it with a bead mill, the dispersion state can be made uniform while maintaining the fiber length. The pressure when using the high pressure homogenizer is preferably 60 to 150 MPa, more preferably 60 to 120 MPa.

[0076] Dispersion methods using a dispersion device include batch dispersion, pass dispersion, circulation dispersion, etc., and any of these methods may be used, or two or more methods may be combined. Batch dispersion is a method in which dispersion is performed using only the dispersion device body without using piping or the like. It is easy to handle, so it is preferable for small-scale production. Pass dispersion is a dispersion method in which the dispersion device body is equipped with a tank that supplies the dispersion liquid through piping and a tank that receives the dispersion liquid, and the dispersion liquid is passed through the dispersion device body. In addition, circulation dispersion is a method in which the dispersion liquid that has passed through the dispersion device body is returned to the tank that supplies the dispersion liquid, and dispersion is performed while circulating. In either case, the longer the processing time, the more the dispersion progresses, so it is sufficient to repeat the pass or circulation until the desired dispersion state is reached, and the processing amount can be increased by changing the size of the tank or the processing time. Pass dispersion is preferable in that it is easier to uniformize the dispersion state compared to circulation dispersion. Circulation dispersion is preferable in that the work and manufacturing equipment are simple compared to pass dispersion. In the dispersion step, the disintegration of aggregated particles, the loosening, wetting, stabilization, etc. of the fibrous carbon proceed sequentially or simultaneously, and the final dispersion state differs depending on how the steps proceed, so it is preferable to control the dispersion state in each dispersion step by using various evaluation methods. For example, the dispersion state can be controlled by the method described in the Examples.

[0077] <Drying process> The method for removing the liquid medium and drying is not particularly limited as long as it can remove the liquid medium from the non-slurry mixture, and examples of the method include drying methods such as hot air drying, vacuum drying, freeze drying, etc. Among these, hot air drying and vacuum drying are preferred from the viewpoint of productivity.

[0078] <Composite for secondary battery electrodes> The composite for a secondary battery electrode contains an electrode active material, fibrous carbon, and may further contain an optional binder resin. The composite for an electrode may further contain optional components.

[0079] The fibrous carbon contained in the electrode composite of the present invention is at least partially crushed and adheres to the surface of the active material.

[0080] The presence of the fibrous carbon in a crushed form on the surface of the active material can efficiently supply electrons required for the battery reaction to the active material, and can also contribute to reducing the contact resistance between active materials when an electrode is fabricated. Therefore, when the fibrous carbon is crushed and uniformly adsorbed on the surface of the active material, and a certain number of aggregates of fibrous carbon are included, when the electrode is used for a secondary battery, the electrode resistance is reduced and the formation of an electronic conduction path to the active material during the battery reaction is favored, thereby improving the battery rate characteristics and cycle characteristics. In addition, since an efficient conductive path can be formed with a small amount of conductive additive, the amount of conductive additive in the electrode can be reduced, and the battery capacity can be improved.

[0081] The crushed form of fibrous carbon refers to a form in which secondary particles (aggregates) of fibrous carbon are broken down into primary particles or a bundle state in which multiple primary particles are bundled together. The state in which fibrous carbon is crushed and adsorbed onto the active material surface includes a state in which the primary particles and / or bundles are isolated, and a state in which the primary particles and / or bundles are overlapped. From the viewpoint of electron supply to the active material and conductive paths between composites, a state in which the primary particles and / or bundles are overlapped and adsorbed in a mesh-like shape is preferred.

[0082] In the present invention, the state in which the fibrous carbon is adsorbed on the surface of the active material in a crushed form means that the area of ​​the fibrous carbon adsorbed on the active material in a crushed fiber state is 10% or more of the entire surface of the active material, preferably 20% or more, and more preferably 50% or more.

[0083] The area occupied by the fibrous carbon adsorbed to the active material in the crushed fiber state can be measured from the contrast difference between the active material and the fibrous carbon in images taken at magnifications of 5,000 to 50,000 times using a scanning electron microscope (SEM) or a scanning electron microscope-energy dispersive X-ray spectroscopy (SEM-EDX), and the average value of the above areas calculated from 20 pieces of active material in the composite was used.

[0084] When the combustion temperature of the fibrous carbon in an oxygen-containing atmosphere is 550° C. or lower, the electrode composite of the present invention becomes a composite in a homogeneous state in which the fibrous carbon adsorbed on the active material surface is loosened.

[0085] The temperature of the exothermic peak in the present invention can be determined by TG-DTA (Thermogravimetry-Differential Thermal Analysis) measurement. Specifically, a TG curve and a DTA curve are obtained by performing TG-DTA measurement under air or oxygen flow conditions. In the obtained DTA curve, the maximum exothermic peak resulting from the combustion of the fibrous carbon, which is located in the vicinity of 300 to 700°C, is read and determined as the temperature of the exothermic peak of the fibrous carbon. This represents the combustion temperature of the fibrous carbon. Generally, fibrous carbon has thick bundles in which primary particles are strongly aggregated by van der Waals forces, and large secondary aggregates in which bundles are aggregated together. The physical properties, such as thermal stability, differ depending on the state of aggregation. Therefore, even for the same type of fibrous carbon, the combustion temperature changes depending on the state of aggregation, and the stronger the aggregation, the higher the combustion temperature.

[0086] The combustion temperature of the fibrous carbon in the secondary battery electrode composite in an oxygen-containing atmosphere is preferably 520°C or less, since the fibrous carbon on the active material is adsorbed in a more loose state, which favors the formation of an electron conduction path from the fibrous carbon to the active material and improves the battery characteristics. It is preferably 480°C or less, and more preferably 450°C or less.

[0087] The secondary battery electrode composite is preferably in the form of particles, and the average particle size is preferably from 0.5 μm to 500 μm, more preferably from 1 μm to 200 μm.

[0088] As mentioned above, when the combustion temperature is 550°C or less and the volume resistivity is 100 Ω·cm or less, the fibrous carbon in the composite is crushed and is thin and uniformly adsorbed on the active material, which is preferable because when used as an electrode for a secondary battery, it reduces the electrode resistance and is favorable for the formation of an electronic conduction path to the active material during the battery reaction, improving the battery rate characteristics and cycle characteristics. In addition, because an efficient conductive path can be formed with a small amount of conductive additive, the amount of conductive additive in the electrode can be reduced, making it possible to improve the battery capacity.

[0089] The content of fibrous carbon in the composite is preferably 0.01% by mass or more, more preferably 0.03% by mass or more, and even more preferably 0.05% by mass or more, based on the mass of the composite for secondary battery electrodes. Also, it is preferably 20% by mass or less, more preferably 10% by mass or less, and even more preferably 5% by mass or less. If it exceeds the above range, the amount of active material filled in the electrode decreases, resulting in a decrease in battery capacity. In particular, for high-capacity batteries, 10% by mass or less is preferable. If it is below the above range, the conductivity of the electrode and battery may be insufficient.

[0090] The composite may contain fibrous carbon other than fibrous carbon. Examples of other fibrous carbon include carbon materials such as carbon black, fullerene, graphene, multilayer graphene, and graphite. Carbon black may be neutral, acidic, or basic, and oxidation-treated carbon black or graphitized carbon black may be used. Other fibrous carbon may be used alone or in combination of two or more.

[0091] <Binder resin> When the secondary battery electrode composition further contains a binder resin, there is no particular restriction as long as it is normally used as a binder resin for paints, and it can be appropriately selected according to the purpose. In addition, the binder resin used in the secondary battery electrode composition is a resin that can bond between active materials, CNTs, other substances such as fibrous carbon, and in this specification, it may be a CMC that has a molecular weight, a degree of etherification, etc. different from the CMC contained in the CNT dispersion of the present invention. Examples of the binder resin used in the secondary battery electrode composition include polymers or copolymers containing ethylene, propylene, vinyl chloride, vinyl acetate, vinyl alcohol, maleic acid, acrylic acid, acrylic acid esters, methacrylic acid, methacrylic acid esters, acrylonitrile, styrene, vinyl butyral, vinyl acetal, vinyl pyrrolidone, etc. as constituent units; polyurethane resins, polyester resins, phenolic resins, epoxy resins, phenoxy resins, urea resins, melamine resins, alkyd resins, acrylic resins, formaldehyde resins, silicone resins, fluororesins; cellulose resins; elastomers such as styrene-butadiene rubber and fluororubber; conductive resins such as polyaniline and polyacetylene. Modified bodies, mixtures, and copolymers of these resins may also be used. Among these, when used as a binder resin for a positive electrode, polymers or copolymers having fluorine atoms in the molecule, such as polyvinylidene fluoride, polyvinyl fluoride, and tetrafluoroethylene, are preferred from the viewpoint of structure. Furthermore, when used as a binder resin for the negative electrode, CMC with good adhesion (however, CMC with a different molecular weight, degree of etherification, etc. from the CMC contained in the CNT dispersion liquid of the present invention), styrene butadiene rubber, polyacrylic acid, etc. are preferred.

[0092] The content of the binder resin in the composite is preferably 0.1% by mass or more, and more preferably 0.3% by mass or more, based on the mass of the active material (the mass of the active material being 100% by mass), and is preferably 20% by mass or less, and more preferably 10% by mass or less.

[0093] <Electrode for secondary batteries> The secondary battery electrode of the present invention includes a composite for a secondary battery electrode. The electrode may further include optional components such as a binder and a dispersant. In general, the electrode is formed by powder compression molding or by applying a composite slurry onto a current collector and removing volatiles.

[0094] The material and shape of the current collector are not particularly limited, and can be appropriately selected from those suitable for various secondary batteries. For example, the material of the current collector can be metals or alloys such as aluminum, copper, nickel, titanium, or stainless steel. In addition, as for the shape, a flat foil is generally used, but a current collector with a roughened surface, a perforated foil, or a mesh-shaped current collector can also be used. The thickness of the current collector is preferably about 0.5 to 30 μm.

[0095] <Method of manufacturing secondary battery electrodes> A secondary battery electrode can be formed by adding a binder or the like to a composite for a secondary battery electrode, forming each component into a sheet by pressing or the like under dry conditions that do not contain solvents, and then powder pressure molding the sheet, or by preparing a composite slurry, coating it on a current collector, and removing the volatile components. The powder pressure molding method without using a composite slurry is preferable because it can reduce the energy consumption required for drying the solvent.

[0096] The method for powder compression molding is not particularly limited, and any known method can be used. When an electrode is produced by powder pressure molding without using a composite material slurry, a dry mixture in which the electrode composite and a binder are mixed in advance, or a dried product after wet mixing may be used. The method for adding a binder or the like to the secondary battery electrode composite and dry-mixing or wet-mixing each component is not particularly limited, and various dispersing machines, mixers, granulators, etc. can be appropriately selected.

[0097] When forming an electrode by adding a binder or the like to a composite for a secondary battery electrode by powder pressure molding and forming each component into a sheet by pressing or the like, each component obtained by adding a binder or the like to a composite for a secondary battery electrode, or a dried product of the dry mixture or wet mixture, may be directly supplied to a current collector and pressure molded, or a free-standing film made of each component obtained by adding a binder or the like to a composite for a secondary battery electrode, or a dried product of the dry mixture or wet mixture, may be prepared in advance and then laminated on a current collector. Also, a thin resin film serving as a binder component may be formed in advance on a current collector.

[0098] Examples of the method for powder pressure molding include a planographic press, a calendar roll, etc. Among them, the use of a calendar roll is preferred because of its productivity and ability to produce uniform molding.

[0099] The method for producing an electrode using the composite slurry is not particularly limited, and a known method can be used.Specific examples include die coating, dip coating, roll coating, doctor coating, knife coating, spray coating, gravure coating, screen printing, and electrostatic painting.As a drying method after coating, standing drying, a blower dryer, a hot air dryer, an infrared heater, a far infrared heater, and the like can be used, but are not particularly limited thereto.

[0100] After the composite slurry is applied, it may be rolled using a lithographic press, a calendar roll, etc. The thickness of the electrode film is, for example, 1 μm or more and 500 μm or less, and preferably 10 μm or more and 300 μm or less.

[0101] <Secondary battery> The secondary battery includes a positive electrode, a negative electrode, and an electrolyte, and at least one selected from the group consisting of the positive electrode and the negative electrode includes an electrode film made from the composite of the present invention.

[0102] The positive electrode may be an electrode film containing a positive electrode active material formed on a current collector, and the negative electrode may be an electrode film containing a negative electrode active material formed on a current collector.

[0103] The electrolyte may be any of a liquid electrolyte, a gel electrolyte, and a solid electrolyte. For example, the liquid electrolyte may contain an electrolyte salt such as a lithium salt and a non-aqueous solvent. As the electrolyte salt, various conventionally known electrolytes capable of moving ions can be used. For example, lithium salts such as LiBF4, LiClO4, LiPF6, LiAsF6, LiSbF6, LiCF3SO3, Li(CF3SO2)2N, LiC4F9SO3, Li(CF3SO2)3C, LiI, LiBr, LiCl, LiAlCl, LiHF2, LiSCN, or LiBPh4 (wherein Ph is a phenyl group) can be used, but are not limited thereto. The electrolyte salt is preferably dissolved in a non-aqueous solvent and used as an electrolytic solution.

[0104] The non-aqueous solvent is not particularly limited, but examples thereof include carbonates such as ethylene carbonate, propylene carbonate, butylene carbonate, dimethyl carbonate, ethyl methyl carbonate, and diethyl carbonate; lactones such as γ-butyrolactone, γ-valerolactone, and γ-octanoic lactone; glymes such as tetrahydrofuran, 2-methyltetrahydrofuran, 1,3-dioxolane, 4-methyl-1,3-dioxolane, 1,2-methoxyethane, 1,2-ethoxyethane, and 1,2-dibutoxyethane; esters such as methyl formate, methyl acetate, and methyl propionate; sulfoxides such as dimethyl sulfoxide and sulfolane; and nitriles such as acetonitrile. These solvents may be used alone or in combination of two or more.

[0105] The secondary battery preferably includes a separator, such as, but not limited to, polyethylene nonwoven fabric, polypropylene nonwoven fabric, polyamide nonwoven fabric, and nonwoven fabrics obtained by subjecting these to hydrophilic treatment.

[0106] The structure of the secondary battery is not particularly limited, but typically includes a positive electrode and a negative electrode, and a separator that is provided as necessary, and can be in various shapes depending on the purpose of use, such as a paper type, a cylindrical type, a button type, or a laminated type.

[0107] The composite for secondary battery electrodes of the present invention is an ideal composite of active material and fibrous carbon, and therefore can be suitably used not only for electrodes made from composite slurries, but also for electrodes made by solid or semi-solid processes. Electrodes made by these solid processes can be applied not only to lithium ion secondary batteries using conventional electrolytes, but also to all-solid batteries and semi-solid batteries.

[0108] The secondary battery of the present invention can be suitably used as a battery for vehicles such as automobiles, and portable electronic devices such as personal computers and smartphones. EXAMPLES

[0109] The present invention will be described in more detail below with reference to examples. The present invention is not limited to the following examples as long as it does not exceed the gist of the invention. Unless otherwise specified, "parts" means "parts by mass" and "%" means "% by mass". In addition, in the examples, "copolymer A" may be referred to as "copolymer" or "dispersant". In addition, in the examples, "dispersant-containing liquid" containing "dispersant" and a solvent may be referred to as "dispersant solution".

[0110] <Polymer synthesis> (Synthesis Example 1) (Synthesis of Dispersant 1) In a reaction vessel equipped with a gas inlet tube, a thermometer, a condenser, and a stirrer, 100 parts of ethyl acetate, 86.0 parts of acrylonitrile, 14.0 parts of acrylic acid, and 0.5 parts of 3-mercapto-1,2-propanediol were charged and replaced with nitrogen gas. The inside of the reaction vessel was heated to 70 ° C, and a mixture consisting of 10 parts of ethyl acetate and 0.4 parts of 2,2'-azobis (2,4-dimethylvaleronitrile) (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.: V-65) was dropped into the reaction vessel over 6 hours to carry out a polymerization reaction. After the dropwise addition, the mixture was reacted at 70 ° C for 1 hour, and then 0.1 parts of V-65 was added, and the reaction was continued at 70 ° C for another 1 hour to obtain the target product as a precipitate. Thereafter, it was confirmed that the conversion rate exceeded 98% by measuring the non-volatile content. The product was filtered by vacuum filtration, washed with 100 parts of ethyl acetate, and the solvent was completely removed by vacuum drying to obtain dispersant 1. Dispersant 1 contains the polymer (A) of the present invention, and trace amounts of component (B) and polymer (E). The content of each structural unit, weight average molecular weight (Mw), content of component (B), and content of polymer (E) shown in Table 1 were as shown in Table 2.

[0111] (Synthesis Example 2) (Synthesis of Dispersant 2) Dispersant 2 was prepared in the same manner as in Production Example 1, except that the monomers used were changed to 72.0 parts of acrylonitrile and 28.0 parts of acrylic acid. The content of each structural unit, the weight average molecular weight (Mw), the content of component (B), and the content of polymer (E) shown in Table 1 were as shown in Table 2. In addition, in the synthesis of the polymer, Mw was adjusted by adding a chain transfer agent, adjusting the amount of polymerization initiator, and changing the reaction conditions, etc.

[0112] (Synthesis Example 3) (Synthesis of Dispersant 3) A reaction vessel equipped with a gas inlet tube, a thermometer, a condenser, and a stirrer was charged with 100 parts of acetonitrile, 86.0 parts of acrylonitrile, 14.0 parts of itaconic acid, and 0.5 parts of 3-mercapto-1,2-propanediol, and replaced with nitrogen gas. The reaction vessel was heated to 70°C, and a mixture consisting of 10 parts of methyl ethyl ketone and 0.4 parts of 2,2'-azobis(2,4-dimethylvaleronitrile) (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.: V-65) was dropped into the reaction vessel over 6 hours to carry out a polymerization reaction. After the dropwise addition, the mixture was reacted at 70°C for 1 hour, and then 0.1 parts of V-65 was added, and the reaction was continued at 70°C for another 1 hour to obtain the target product as a precipitate. Thereafter, it was confirmed that the conversion rate exceeded 98% by measuring the nonvolatile content. The product was filtered off by vacuum filtration, washed with 100 parts of ethyl acetate, and the solvent was completely removed by vacuum drying to obtain dispersant 3. The content of each structural unit, the weight average molecular weight (Mw), the content of component (B), and the content of polymer (E) shown in Table 1 were as shown in Table 2.

[0113] (Synthesis Example 4) (Synthesis of Dispersant 4) Dispersant 4 was produced in the same manner as in Production Example 1, except that the monomers used were changed to 86.0 parts of methacrylonitrile and 14.0 parts of itaconic acid. The content of each structural unit, weight average molecular weight (Mw), content of component (B), and content of polymer (E) shown in Table 1 were as shown in Table 2. In addition, in the synthesis of the polymer, Mw was adjusted by adding a chain transfer agent, adjusting the amount of polymerization initiator, and appropriately changing the reaction conditions, etc.

[0114] (Synthesis Example 5) (Synthesis of Dispersant 5) In a reaction vessel equipped with a gas inlet tube, a thermometer, a condenser, and a stirrer, 100 parts of methanol, 65.0 parts of acrylonitrile, 35.0 parts of vinyl acetate, and 0.5 parts of 3-mercapto-1,2-propanediol were charged and replaced with nitrogen gas. The reaction vessel was heated to 70°C, and a mixture consisting of 10 parts of methyl ethyl ketone and 0.4 parts of 2,2'-azobis(2,4-dimethylvaleronitrile) (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.: V-65) was dropped into the reaction vessel over 6 hours to carry out a polymerization reaction. After the dropwise addition, the mixture was reacted at 70°C for 1 hour, and then 0.1 parts of V-65 was added, and the reaction was continued at 70°C for another 1 hour to obtain a copolymer / methanol mixture. Next, 40 parts of 2mol / L sodium hydroxide / methanol solution was added as sodium hydroxide, and the temperature was raised to 60°C, and the mixture was reacted for 4 hours to completely saponify the mixture. The product was then filtered off under reduced pressure, washed with 100 parts of methanol and then with 100 parts of ethyl acetate, and the solvent was completely removed by drying under reduced pressure to obtain Dispersant 5. The content of each structural unit, the weight average molecular weight (Mw), the content of component (B), and the content of polymer (E) shown in Table 1 were as shown in Table 2. It was confirmed that some of the cyano groups had been modified to amide groups by the sodium hydroxide used in the saponification reaction.

[0115] (Synthesis Example 6) (Synthesis of Dispersant 6) In a reaction vessel equipped with a gas inlet tube, a thermometer, a condenser, and a stirrer, 100 parts of methanol, 67.0 parts of acrylonitrile, 8.0 parts of acrylic acid, 35.0 parts of vinyl acetate, and 1.0 parts of 3-mercapto-1,2-propanediol were charged and replaced with nitrogen gas. The reaction vessel was heated to 70°C, and a mixture consisting of 10 parts of methyl ethyl ketone and 0.4 parts of 2,2'-azobis(2,4-dimethylvaleronitrile) (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.: V-65) was dropped into the reaction vessel over 6 hours to carry out a polymerization reaction. After the dropwise addition, the mixture was reacted at 70°C for 1 hour, and then 0.1 parts of V-65 was added, and the reaction was continued at 70°C for another 1 hour to obtain a copolymer / methanol mixture. Next, 40 parts of 2mol / L sodium hydroxide / methanol solution was added as sodium hydroxide, and the temperature was raised to 60°C, and the mixture was reacted for 4 hours to completely saponify the mixture. The product was then filtered off under reduced pressure, washed with 100 parts of methanol and then with 100 parts of ethyl acetate, and the solvent was completely removed by drying under reduced pressure to obtain Dispersant 6. The content of each structural unit, the weight average molecular weight (Mw), the content of component (B), and the content of polymer (E) shown in Table 1 were as shown in Table 2. It was confirmed that some of the cyano groups had been modified to amide groups by the sodium hydroxide used in the saponification reaction.

[0116] (Synthesis Example 7) (Synthesis of Dispersant 7) In a reaction vessel equipped with a gas inlet tube, a thermometer, a condenser, and a stirrer, 100 parts of methanol, 0.1 parts of diethanolamine, and 5 parts of sodium hypophosphite were charged and replaced with nitrogen gas. The reaction vessel was heated to 70°C, and 65 parts of acrylonitrile and 35 parts of N-vinyl-2-pyrrolidone were added dropwise over 2 hours. Subsequently, an aqueous initiator solution consisting of 2 parts of 2,2'-azobis-2-amidinopropane dihydrochloride (manufactured by Fujifilm Wako Pure Chemical Industries: V-50) and 18 parts of ion-exchanged water was added dropwise over 1.5 hours. After the addition was completed, the mixture was reacted for 3.5 hours, and then an aqueous solution consisting of 0.1 parts of V-50 and 0.9 parts of ion-exchanged water was added, and after another 30 minutes, an aqueous solution consisting of 0.1 parts of V-50 and 0.9 parts of ion-exchanged water was added again. After 4.5 hours from the start of polymerization, it was confirmed that the conversion rate had reached 95%, and 0.5 parts of a 10% aqueous malonic acid solution was added as a pH adjuster to obtain an aqueous dispersion of the polymer. The mixture was then filtered under reduced pressure, washed with methanol, and the solvent was completely removed by drying under reduced pressure to obtain Dispersant 7. The content of each structural unit, weight average molecular weight (Mw), content of component (B), and content of polymer (E) shown in Table 1 were as shown in Table 2.

[0117] (Synthesis Example 8) (Synthesis of Dispersant 8) In a reaction vessel equipped with a thermometer, a condenser, and a stirrer, 1000 parts of ion-exchanged water, 95 parts of acrylic acid, 5 parts of acrylonitrile, and 5 parts of ammonium persulfate (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) as a polymerization initiator were added, heated to 70°C, and stirred at 70°C for 300 minutes (5 hours). When the conversion rate reached 90% or more, the mixture was cooled to terminate the reaction. Thereafter, the pH was adjusted to 8.0 with a 4% aqueous sodium hydroxide solution, and the unreacted raw materials were reduced by heating and vacuum distillation to obtain an aqueous solution of a polymer. Half of the aqueous solution of the polymer was removed and dried to obtain comparative dispersant 2. A four-necked separable flask was charged with 250 parts of methyl ethyl ketone and 250 parts of methanol, and the flask was rotated 1,000 times with a disperser, and the remaining aqueous solution of the polymer was added dropwise over 1 hour. The white precipitate that had formed was removed by filtration and dried under reduced pressure to obtain dispersant 8. The content of each structural unit, the weight average molecular weight (Mw), the content of component (B), and the content of polymer (E) shown in Table 1 were as shown in Table 2.

[0118] (Synthesis Example 9) (Synthesis of Dispersant 9) A reaction vessel equipped with a gas inlet tube, a thermometer, a condenser, and a stirrer was charged with 50 parts of ion-exchanged water, 50 parts of methanol, 0.1 parts of diethanolamine, 5 parts of sodium hypophosphite, 27 parts of 2-hydroxyethyl acrylate, and 73 parts of N-vinyl-2-pyrrolidone, and the atmosphere was replaced with nitrogen gas. The inside of the reaction vessel was heated to 70°C and maintained for 2 hours. An aqueous initiator solution consisting of 2 parts of 2,2'-azobis-2-amidinopropane dihydrochloride (manufactured by Fujifilm Wako Pure Chemical Industries: V-50) and 18 parts of ion-exchanged water was added dropwise over 1.5 hours. After the dropwise addition, the mixture was reacted for 3.5 hours, and then an aqueous solution consisting of 0.1 parts of V-50 and 0.9 parts of ion-exchanged water was added. After 30 minutes, an aqueous solution consisting of 0.1 parts of V-50 and 0.9 parts of ion-exchanged water was added again. The conversion rate was confirmed to be 90%, and 1.4 parts of a 10% aqueous malonic acid solution was added as a pH adjuster to obtain an aqueous dispersion of the polymer. The mixture was filtered under reduced pressure, washed with a mixture of 50 parts of methanol and 50 parts of ion-exchanged water, and then dried under reduced pressure to completely remove the solvent, obtaining a dispersant 9. The content of each structural unit, weight average molecular weight (Mw), content of component (B), and content of polymer (E) shown in Table 1 were as shown in Table 2.

[0119] (Synthesis Example 10) (Synthesis of Dispersant 10) A reaction vessel equipped with a gas inlet tube, a thermometer, a condenser, and a stirrer was charged with 100 parts of methanol and 100 parts of vinyl acetate, and the atmosphere was replaced with nitrogen gas. The reaction vessel was heated to 50°C, and 0.5 parts of 2,2'-azobis(2-methylpropionic acid methyl ester) (Fujifilm Wako Pure Chemical Industries: V-601) was dropped into the reaction vessel over 4 hours to carry out a polymerization reaction. After the dropwise addition was completed, the reaction was maintained at the same temperature for another 2 hours. When the conversion rate reached 95% or more, the reaction was terminated by cooling, and a polyvinyl acetate / methanol solution was obtained. Subsequently, 60 parts of 2 mol / L sodium hydroxide / methanol solution (0.4 equivalents relative to the amount of acetic acid charged) were added as sodium hydroxide, and the temperature was raised to 60°C and the reaction was carried out for 4 hours, resulting in a polyvinyl alcohol / methanol mixture with a saponification degree of 86 mol%. The white solid obtained by drying under reduced pressure was pulverized in an agate mortar, suspended by ultrasonic irradiation in a mixed solution of 100 parts of methanol and 100 parts of methyl ethyl ketone, filtered, and dried under reduced pressure to obtain Dispersant 10. The content of each structural unit, weight average molecular weight (Mw), content of component (B), and content of polymer (E) shown in Table 1 were as shown in Table 2.

[0120] (Synthesis Example 11) (Synthesis of Dispersant 11) In a reaction vessel equipped with a gas inlet tube, a thermometer, a condenser, and a stirrer, 100 parts of methanol and 100 parts of vinyl acetate were charged and replaced with nitrogen gas. The inside of the reaction vessel was heated to 50°C, and 0.5 parts of 2,2'-azobis(2-methylpropionic acid methyl ester) (Fujifilm Wako Pure Chemical Industries: V-601) was dropped into the reaction vessel over 4 hours to carry out a polymerization reaction. After the dropwise addition, the reaction was held at the same temperature for another 2 hours. When the conversion rate reached 95% or more, the reaction was terminated by cooling, and a polyvinyl acetate / methanol solution was obtained. Subsequently, 80 parts of 2mol / L sodium hydroxide / methanol solution was added as sodium hydroxide, and the temperature was raised to 70°C and the reaction was carried out for 5 hours to obtain a polyvinyl alcohol / methanol mixture with a saponification degree of 98mol%. Next, 800 parts by mass of ion-exchanged water was added to dissolve the polyvinyl alcohol, and 2 parts by mass of hydrochloric acid and 20 parts by mass of butyl aldehyde were dropped while stirring. The temperature was raised to 80°C and maintained for 1 hour to convert some of the hydroxyl groups to butyral, and the reaction was stopped by cooling. 250 parts of methyl ethyl ketone and 250 parts of methanol were charged into a four-necked separable flask, and the polymer solution was added dropwise over 1 hour while the flask was rotated at 1,000 revolutions in a disperser. The white precipitate formed was filtered out and dried under reduced pressure to obtain dispersant 11. The content of each structural unit, weight average molecular weight (Mw), content of component (B), and content of polymer (E) shown in Table 1 were as shown in Table 2.

[0121] (Synthesis Example 12) (Synthesis of Dispersant 12) In a reaction vessel equipped with a gas inlet tube, a thermometer, a condenser, and a stirrer, 100 parts of ion-exchanged water, 0.1 parts of diethanolamine, and 5 parts of sodium hypophosphite were charged, and the atmosphere was replaced with nitrogen gas. The reaction vessel was heated to 90°C, and 100 parts of N-vinyl-2-pyrrolidone was added dropwise over 2 hours. Subsequently, an aqueous initiator solution consisting of 2 parts of 2,2'-azobis-2-amidinopropane dihydrochloride (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.: V-50) and 18 parts of ion-exchanged water was added dropwise over 1.5 hours. After the dropwise addition, the mixture was reacted for 3.5 hours, and then an aqueous solution consisting of 0.1 parts of V-50 and 0.9 parts of ion-exchanged water was added, and after another 30 minutes, an aqueous solution consisting of 0.1 parts of V-50 and 0.9 parts of ion-exchanged water was added again. After 4.5 hours from the start of polymerization, it was confirmed that the conversion rate had reached 90%, and 1.4 parts of a 10% aqueous malonic acid solution was added as a pH adjuster to obtain an aqueous dispersion of the polymer. The mixture was then filtered under reduced pressure, washed with 100 parts of ion-exchanged water, and the solvent was completely removed by drying under reduced pressure to obtain a dispersant 12. The content of each structural unit, weight average molecular weight (Mw), content of component (B), and content of polymer (E) shown in Table 1 were as shown in Table 2.

[0122] [Table 1]

[0123] [Table 2]

[0124] (Method of measuring weight average molecular weight (Mw) of polymer (A) and content of polymer (E)) The weight average molecular weight (Mw) of the synthesized polymer (A) and the content of the polymer (E) were measured by gel permeation chromatography (GPC) equipped with an RI detector, selecting either measurement method 1 or measurement method 2 depending on the solubility of the dispersant in water. The dispersant was added to a mixture of purified water / methanol = 3 / 7 (volume ratio) so as to be 0.2 mass%, and ultrasonicated for 10 minutes. If the dispersant was completely dissolved, it was measured by measurement method 1. If the dispersant was not completely dissolved and precipitates were generated or it was in a suspended state, it was measured by measurement method 2. (Measurement method 1) The device used was Shodex GPC-101 (Showa Denko K.K.), and three Showa Denko K.K. "OHpak°SB-806M°HQ" and one Showa Denko K.K. "OHpak°SB-802.5°HQ" were connected in series as separation columns, for a total of four columns. The oven temperature was 40°C, and a 50 mM lithium chloride purified water / methanol = 3 / 7 (volume ratio) solution was used as the eluent, and the measurement was performed at a flow rate of 1.0 mL / min. The sample was prepared in a mixture of the above eluent at a concentration of 0.2 mass%, and 0.1 mL was injected. The molecular weight is a polyethylene glycol equivalent value. From the above measurement results, the weight average molecular weight (Mw) of the polymer (A) and the content of the polymer (E) having a molecular weight of less than 1,000 were calculated. (Measurement method 2) The device used was a HLC-8320GPC (manufactured by Tosoh Corporation), and the separation columns were Tosoh Corporation's "TSK-GELSUPERAW-4000", "AW-3000", and "AW-2500" connected in series, with the oven temperature at 40°C, an N,N-dimethylformamide solution of 30 mM triethylamine and 10 mM lithium bromide as the eluent, and the measurement was performed at a flow rate of 0.6 mL / min. The sample was prepared in a solvent consisting of the above eluent at a concentration of 0.2 mass%, and 10 μL was injected. The molecular weight is a polystyrene equivalent value. From the above measurement results, the weight average molecular weight (Mw) of the polymer (A) and the content of the polymer (E) having a molecular weight of less than 1,000 were calculated.

[0125] The amount of component (B) contained in the dispersant was calculated from the sum of the content of the volatile components and the content of sodium acetate, which were determined as follows. The content of component (B) contained in each dispersant is shown in Table 2.

[0126] (Quantitative analysis of volatile components) The content of the volatile components in the obtained dispersant was calculated by subtracting the amount of moisture quantified by Karl Fischer from the weight loss when heat-treated in a hot air oven. Approximately 0.5 g of the sample was collected and spread on an aluminum dish, left to stand in a hot air oven at 150 ° C for 10 minutes, then cooled in a desiccator for 3 minutes, and the weight after quick drying was measured, and the weight loss rate G1 (%) was calculated. The moisture content G2 (%) was measured by treating the sample at 150 ° C under a nitrogen gas flow of 250 ml / min using a Karl Fischer moisture meter (tabletop coulometric moisture meter CA-200 type: manufactured by Mitsubishi Chemical Analytech Co., Ltd., catholyte: manufactured by Mitsubishi Chemical Corporation, Aquamicron (trademark) CXU, anolyte: manufactured by Mitsubishi Chemical Corporation, Aquamicron (trademark) AX) by the Karl Fischer method. The content of the volatile components was calculated as G1-G2 (%).

[0127] When each dispersant was analyzed by gas chromatography, compounds 11 to 13 listed in Table 3 were detected in dispersants 1 to 6, compounds 14 to 16 in dispersants 7, 9, and 12, compound 17 in dispersant 8, and compounds 18 to 20 in dispersants 10 and 11, which were compounds generated when the polymerization initiator was deactivated without polymerization.

[0128] [Table 3]

[0129] (Analysis of the content of structural units in polymer (A) by nuclear magnetic resonance) The contents of the nitrile group-containing structural unit, the carboxyl group-containing structural unit, the hydroxyl group-containing structural unit, and the heterocyclic ring-containing structural unit were determined using a nuclear magnetic resonance apparatus (ADVANCE400Nanobay: manufactured by Bruker Japan) from 1H-NMR quantitative spectrum using a measurement solvent (D3C)2S=O and a 1 mm NMR tube, and 13C-NMR quantitative spectrum using a measurement solvent (D3C)2S=O and a 10 mm NMR tube. However, when peaks derived from a structure in which a polymerization initiator or a chain transfer agent is bound to the polymer were detected, they were excluded from the content of each structural unit in the polymer (A) in the calculation.

[0130] <Preparation of fibrous carbon dispersion> (Production Example 1) According to the composition shown in Table 4, a total of 1 kg of ion-exchanged water, dispersant, and additives were added to a stainless steel container and stirred with a disperser until it was uniform. Then, fibrous carbon was added while stirring with a disperser, and a square-hole high-shear screen was attached to a high-shear mixer (L5M-A, manufactured by SILVERSON). Batch dispersion was performed at a speed of 8,000 rpm until the entire mixture became uniform and the dispersion particle size was 250 μm or less using a grind gauge. At this time, the dispersion particle size confirmed by the grind gauge was 180 μm. Next, the liquid to be dispersed was supplied from the stainless steel container to a high-pressure homogenizer (Starburst Lab HJP-17007, manufactured by Sugino Machine) through a pipe, and 20 passes of dispersion processing were performed until D50 was 100 μm or less. The dispersion processing was performed using a single nozzle chamber with a nozzle diameter of 0.25 mm and a pressure of 100 MPa. The obtained fibrous carbon dispersion (dispersion 1) had low viscosity and good storage stability.

[0131] (Examples 2 to 13) Each dispersion (Dispersions 2 to 13) was obtained in the same manner as in Production Example 1, according to the composition shown in Table 4. However, when the median diameter was 100 μm or more, an additional two-pass dispersion treatment was performed, and the measurement was repeated until the median diameter was 100 μm or less. All of the fibrous carbon dispersions of the present invention (Dispersions 2 to 16) had low viscosity and good storage stability.

[0132] (Method of measuring the dispersed particle size of fibrous carbon dispersion) The particle size distribution was determined using a grind gauge with a maximum groove depth of 300 μm, according to a method conforming to JIS K5600-2-5.

[0133] (Method for measuring particle size distribution using dynamic light scattering) After leaving the fibrous carbon dispersion in a thermostatic bath at 25°C for more than 1 hour, the fibrous carbon dispersion was thoroughly stirred and diluted, and then the cumulative particle size D10 and cumulative particle size D50 of the fibrous carbon dispersion were measured using a particle size distribution meter (Microtrack Bell Co., Ltd., NanotracUPA, modelUPA-EX). The particle refractive index of the carbon-based fibrous carbon was 1.8, and the shape was aspherical. The refractive index of the solvent was 1.333. When measuring, the concentration of the CNT dispersion was diluted so that the loading index value was in the range of 0.8 to 1.2. Criterion D10 ◎: 100nm or more and less than 400nm (excellent) ○: 50nm or more and less than 100nm (good) Judgment standard D50 ◎: 200nm or more and less than 1,500nm (excellent) ○: 1,500nm or more and less than 3,000nm (good)

[0134] (Complex modulus and phase angle of fibrous carbon dispersion) The complex modulus and phase angle of the fibrous carbon dispersion were evaluated by performing dynamic viscoelasticity measurements at 25°C, a frequency of 1 Hz, and a strain rate range of 0.01% to 5% using a rheometer (RheoStress1 rotational rheometer manufactured by ThermoFisherScientific Co., Ltd.) with a cone diameter of 35 mm and 2°. Criterion complex modulus ◎: 10 Pa or more and less than 50 Pa (excellent) ○: 5 Pa or more but less than 10 Pa (good) △: Less than 5 Pa (poor) Judgment criteria phase angle ◎: 10° to less than 50° (excellent) ○: 3° or more and less than 10° (good) △: Less than 3° (poor)

[0135] (Viscosity of fibrous carbon dispersion) The fibrous carbon dispersion was allowed to stand in a thermostatic bath at 25°C for at least 1 hour, and then thoroughly stirred. The shear viscosity was then evaluated at 25°C and at shear rates of 1 s-1 and 10 s-1 using a rheometer (RheoStress1 rotational rheometer manufactured by ThermoFisherScientific Co., Ltd.) with a cone diameter of 35 mm and 2°. Judgment standard 1 / s ◎: 5,000 Pa·s or more and less than 30,000 Pa·s (excellent) ○: 500 Pa·s or more and less than 5,000 Pa·s (good) Judgment criteria 10 / s ◎: 500 Pa·s or more and less than 3,000 Pa·s (excellent) ○: 100 Pa·s or more and less than 500 Pa·s (good)

[0136] [Table 4]

[0137] The raw materials listed in Table 4 are as follows. BT1003M: LUCANBT1003M (LGchem Ltd., multi-walled CNT, average outer diameter 13 nm, average fiber diameter 32 μm, specific surface area 201 m2 / g) ·6A:JENOTUBE6A (manufactured by JEIO, multilayer CNT, average outer diameter 6nm, average fiber diameter 58μm, specific surface area 700m2 / g)

[0138] <Electrode composite for secondary batteries> (Example 1-1) According to the composition shown in Table 5, an electrode composite for a secondary battery was produced as follows. First, the fibrous carbon dispersion 1 was placed in a stainless steel container, and ion-exchanged water was added while stirring with a disperser, and the mixture was stirred for 10 minutes. Next, LFP and the above dispersion were placed in a container of a Mechanofusion (AMS-MINI, manufactured by Hosokawa Micron Corporation), and the mixture was stirred for 15 minutes at a rotation speed of 5000 rpm to prepare a mixture. During stirring, the temperature was controlled at 25°C with a temperature-controlling chiller. The mixture was then taken out into a stainless steel vat and vacuum-dried at 80°C for 1 hour using a vacuum dryer to completely remove the solvent. The dried product was coarsely crushed in a mortar to obtain a secondary battery electrode composite 1.

[0139] (Examples 1-2 to 1-13) According to the compositions shown in Table 5, Composites 2 to 13 were obtained in the same manner as in Example 1-1.

[0140] (Comparative Example 1-1) An electrode composite for a secondary battery was prepared as follows according to the composition shown in Table 5. LFP and fibrous carbon were charged into a container of Mechanofusion (AMS-MINI, manufactured by Hosokawa Micron Corporation) and stirred at a rotation speed of 5000 rpm for 15 minutes to prepare an electrode composite for a secondary battery 14. During stirring, the temperature was controlled at 25°C using a temperature-controlling chiller.

[0141] (Comparative Example 1-2) According to the composition shown in Table 5, an electrode composite for a secondary battery was prepared as follows. First, the fibrous carbon dispersion 1 was placed in a stainless steel container, and ion-exchanged water was added while stirring with a disperser, and the mixture was stirred for 10 minutes. Next, LFP and the above dispersion were charged into a Trimix (TX-2L, manufactured by Inoue Seisakusho Co., Ltd.) container, and the mixture was stirred for 30 minutes at a rotation speed (revolution) of 50 rpm to prepare a mixture. During stirring, the temperature was controlled at 25°C with a temperature-controlling chiller. After that, the mixture obtained was taken out into a stainless steel vat and vacuum-dried at 80°C for 3 hours using a vacuum dryer to completely remove the liquid component. The dried product was coarsely crushed in a mortar to obtain an electrode composite for a secondary battery 15.

[0142] (Comparative Example 1-3) According to the composition shown in Table 5, Composite 16 was obtained in the same manner as in Comparative Example 1-2.

[0143] <Evaluation of the state of fibrous carbon in composites> The dispersion state of the fibrous carbon in the composite was determined using a JEOL JSM-7800F scanning electron microscope. Criteria for determining the surface disintegration state of fibrous carbon active material ◎: The area of ​​fibrous carbon adsorbed on the active material in a crushed fiber state is 40% or more of the entire surface area of ​​the active material. ○: The area of ​​the fibrous carbon adsorbed on the active material in a crushed state is 20% or more and less than 40% of the entire surface of the active material. △: The area of ​​the fibrous carbon adsorbed on the active material in a crushed state is 10% or more and less than 20% of the entire surface area of ​​the active material. ×: The fibers are not adsorbed to the active material in a crushed state.

[0144] <Exothermic peak temperature of fibrous carbon> The exothermic peak temperature of the fibrous carbon was evaluated using a differential thermobalance ThermoplusEV02TG8121 manufactured by Rigaku. Compressed air was flowed at 200 mL / min, and the exothermic peak temperature obtained when the temperature was increased from 40°C to 800°C at 10°C / min was used as an index. The exothermic peak temperature was calculated by reading the peak top temperature of the exothermic peak of the fibrous carbon in the range of 400 to 700°C in the DTA curve obtained by measurement.

[0145] [Table 5]

[0146] The abbreviations used in Table 5 have the following meanings: LFP: Lithium iron phosphate HED (trademark) LFP-400 (BASF, 100% non-volatile content)

[0147] As shown in Table 5, in the examples, the composite state of the fibrous carbon was more uniform than in the comparative examples, and excellent powder resistance was shown. In the examples, the fibrous carbon in the composite was loosened and adsorbed on the surface of the active material without excessive aggregation. Therefore, it is presumed that the conductive path between the composites could be formed uniformly, leading to a reduction in powder resistance. On the other hand, in the comparative example, insufficient crushing of the fibrous carbon during the composite manufacturing process and excessive drying and aggregation during the drying process cause a decrease in the amount of adsorption onto the active material surface and uneven distribution of the material, resulting in non-uniform formation of conductive paths between the composites. If the fibrous carbon in the composite is compounded in a non-uniform state, when an electrode is formed, the conductive paths, composition, and strength become non-uniform, which causes deterioration of the electrode resistance and deterioration of battery performance such as rate characteristics and cycle characteristics. From the above, it is shown that the electrode composite produced by the production method of the present invention has a homogeneous and excellent composite state and powder resistance, and is expected to exhibit excellent battery characteristics.

Claims

1. A method for producing a composite for a secondary battery electrode, comprising: The method includes a step of combining an electrode active material and a fibrous carbon dispersion in which fibrous carbon is dispersed in a solvent in a non-slurry state using a mechanochemical mixer, and a step of removing the solvent and drying the resulting mixture, The fibrous carbon dispersion comprises a dispersant composition that satisfies the following (1) and (2); The present invention comprises fibrous carbon having an average fiber length of 0.3 μm or more and a medium containing water, A method for producing a secondary battery electrode composite, comprising: (1) Nitrile group-containing structural unit, carboxyl group-containing structural unit, hydroxyl group-containing structure units, and heterocyclic ring-containing structural units, The polymer (A) has a weight average molecular weight of 5,000 or more and 360,000 or less. (2) A component (B) other than the polymer, which is derived from the raw material of the polymer (A), is added to the dispersant composition. The content is 2% by mass or less based on mass. (3) A particle size D10 at 10% cumulative particle size distribution measured by dynamic light scattering is 50n m or more.

2. 2. The method for producing a composite for a secondary battery electrode according to claim 1, wherein the fibrous carbon dispersion has a particle diameter D50 at a cumulative 50% of a particle size distribution measured by a dynamic light scattering method of less than 3000 nm.

3. 3. The method for producing a composite for a secondary battery electrode according to claim 1, wherein the polymer (A) contains 5 mass% or less of a polymer (E) having a molecular weight of less than 1,000 based on the mass of the polymer (A).

4. 3. The method for producing a composite for a secondary battery electrode according to claim 1, wherein the fibrous carbon has an exothermic peak temperature of 520° C. or less, as determined by simultaneous thermogravimetry and differential thermal analysis in an oxygen atmosphere.

5. 3. The method for producing a composite for a secondary battery electrode according to claim 1, wherein the composite for a secondary battery electrode contains a binder resin.

6. A method for producing an electrode film formed by using the electrode composite for secondary batteries obtained by the method for producing an electrode composite for secondary batteries according to claim 1 or 2.

7. A method for producing a secondary battery comprising an electrode film obtained by the method for producing an electrode film according to claim 6.

Citation Information

Patent Citations

  • Hydraulic clutch switch valve

    JP1978077946A

  • Optical processing apparatus

    JP1988080526A

  • Active material and battery using the same

    JP2016201228A

  • Composite particles for electrochemical element electrodes, electrochemical element electrodes, and electrochemical elements

    JP6954424B2